2013
DOI: 10.1021/ja404784t
|View full text |Cite
|
Sign up to set email alerts
|

A Mechanistic Rationale for the 9-Amino(9-deoxy)epi Cinchona Alkaloids Catalyzed Asymmetric Reactions via Iminium Ion Activation of Enones

Abstract: The 9-amino(9-deoxy)epi cinchona alkaloids have expanded the synthetic potential of asymmetric aminocatalysis, enabling the highly stereoselective functionalization of a variety of sterically hindered carbonyl compounds. However, there is a lack of basic understanding of the mechanisms of cinchona-based primary aminocatalysis. Herein, we describe how a combination of experimental and theoretical mechanistic studies has revealed the origin of the stereoselectivity of the Friedel-Crafts alkylation of indoles wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
45
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 74 publications
(50 citation statements)
references
References 66 publications
5
45
0
Order By: Relevance
“…Although the origin of stereochemistry in the Michael addition fits the model proposed by Melchiorre and co‐workers (Figure a), which describes optimal conditions of 2:1 co‐catalyst to amine catalyst, we found that better yields were obtained in a 1:2 ratio (Table , entry 11). We, therefore, do not discount the possibility of a bifunctional effect of the catalyst on the enantioselective outcome (Figure b), as has been described for other related processes, although further study is required.…”
Section: Figuresupporting
confidence: 75%
See 1 more Smart Citation
“…Although the origin of stereochemistry in the Michael addition fits the model proposed by Melchiorre and co‐workers (Figure a), which describes optimal conditions of 2:1 co‐catalyst to amine catalyst, we found that better yields were obtained in a 1:2 ratio (Table , entry 11). We, therefore, do not discount the possibility of a bifunctional effect of the catalyst on the enantioselective outcome (Figure b), as has been described for other related processes, although further study is required.…”
Section: Figuresupporting
confidence: 75%
“… (a) Although the stereoselective outcome of our process fits the model of Melchiorre our stoichiometry and co‐catalyst are slightly different. (b) Bifunctional activation of the enone and nucleophile is also a possibility …”
Section: Figurementioning
confidence: 90%
“…6). This class of compounds, derived from natural sources, has been identified as a promising alternative to other amino‐catalysts such as proline . ( A ) As well as its quinidine diasteteroisomer activate various carbonyl compounds with a consistently high level of stereocontrol.…”
Section: Resultsmentioning
confidence: 99%
“…According to our simulations, the rich conformational behavior of (A) is not easily rationalized in terms of four relevant (anti/syn and closed/open) conformations. [132,134] The 2D conformational map with 5, 10, 15, and 20 kcal mol 21 isocontours given in Figure 6 suggests a somewhat richer conforma-tional picture consisting of four easily accessible conformational regions (1)(2)(3)(4) and one that is less frequently visited (2 0 ). The most populated region, 1, essentially encompasses a 608 range for the C 8 AC 9 AC 0 4 AC 4a angle with no significant energy barrier.…”
Section: Full Papermentioning
confidence: 99%
See 1 more Smart Citation